Antimicrobial photodynamic therapy mediated by methylene blue-loaded polymeric micelles against Streptococcus mutans and Candida albicans biofilms - Soares, Jonas Corsino Maduro [UNESP]; Luiz, Marcela Tavares [UNESP]; Oshiro Junior, João Augusto [UNESP]; Besegato, João Felipe [UNESP]; de Melo, Priscila Borges Gobbo [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2023)
Background: Streptococcus mutans and Candida albicans can colonize the teeth, the oral cavity as biofilm and can cause oral infections. Thus, strategies to prevent and control oral biofilms are requested. The present study aims the development and characterization of methylene blue (MB)-loaded polymeric micelles for antimicrobial photodynamic therapy (aPDT) against Streptococcus mutans and Candida albicans biofilms Methods: MB-loaded polymeric micelles were produced and characterized by particle size, polydispersity index, morphology, zeta potential, stability, MB release profile, and antimicrobial effect against S. mutans and C. albicans biofilms. Results: MB-loaded polymeric micelles showed a reduced particle size, moderate polydisperse profile, spherical and neutral shape, which demonstrated to be promising features to allow micelles penetration into biofilms. Antimicrobial effect against bacterial and yeast biofilms was demonstrated once MB was irradiated by light under 660 nm (aPDT). Furthermore, MB-loaded polymeric micelles showed significant inhibition of S. mutans and C. albicans biofilms. Furthermore, the treatment with MB-micelles incubated with high pre-incubation times (15 and 30 min) were more effective than 5 min. It can be explained by the time required for this nanosystem to penetrate the innermost layer of biofilms and release MB for aPDT. Conclusion: MB-loaded polymeric micelles can effectively decrease the bacteria and yeast viability and it may cause positive impacts in the clinical practice. Thus, the developed formulation showed potential in the treatment to remove oral biofilms, but clinical studies are needed to confirm its potential
Keywords: Methylene blue; Nanoparticles; Nanosystems; Photodynamic therapy; photosensitizer; Pluronic® F127; Poloxamer 407